Diesel engine waste heat recovery system comprehensive optimization based on system and heat exchanger simulation - Li Da (De Gruyter, 2021)
To further improve the thermal efficiency of diesel engines, a waste heat recovery system model utilizing organic Rankine cycle (ORC) is constructed and verified through system bench test and heat exchanger bench test. To recover waste heat from diesel engine exhaust, ethanol, cyclopentane, cyclohexane, R1233zd (E), and R245fa were selected for comparison. The quality of heat source, the quality of evaporator, the system output, and the system complicity were taken as variables for comparison. Analysis shows that for ORC systems without recuperator, ethanol system has the best system output of the five in a wide operation temper range, with the highest exergy efficiency of 24.1%, yet the exergy efficiency increase after the application of recuperator, 9.0%, is limited. For low temperature exhaust, cyclopentane system has the best performance with or without recuperator, and the cyclopentane system with recuperator has the best performance in terms of exergy efficiency, 27.6%, though complex heat exchangers are also required for high power output. The system output of the R1233zd system is better than the R245fa system, yet the advantage of low evaporate temperature can be better utilized for low quality waste heat recovery.